Role of Anions in 5‐Hydroxymethylfurfural Solvation in Ionic Liquids from Molecular Dynamics Simulations. Issue 12 (9th October 2022) - Montes‐Campos, Hadrián; Méndez‐Morales, Trinidad; Varela, Luis Miguel; Ortuño, Manuel Angel
Abstract: The proper selection of solvents for biomass upgrading is a crucial task as it should carefully balance the enhancement of reactivity with a facile product recovery. A challenging case is the conversion of glucose and fructose to 5‐hydroxymethylfurfural (HMF). Ionic liquids (ILs) are often employed to boost the activity and selectivity of this process, although the isolation of HMF from the medium remains a major drawback. To investigate such solvent effects in a realistic (dynamic) environment, classical molecular dynamics (MD) simulations of HMF are performed in imidazolium‐based ILs with different anions. Several parameters are identified that directly control HMF–anion interactions, which may hamper product separation, as well as HMF–HMF contacts, which can promote undesired side‐reactions. These computational results would guide future high‐throughput screenings of new and improved IL media. Abstract : Classical molecular dynamics simulations of 5‐hydroxymethylfurfural in ionic liquids reveal key parameters that control solute–solute and solute–solvent interactions. These tools would drive the design of new reaction media that both enhance product separation and prevent undesired side‐reactions. Institute and/or researcher Twitter usernames: @ChemOrtuno @ciqususc @UniversidadeUSC